Treating non-insulin-dependent diabetes. Oral agents or insulin? - Shlossberg, A. H. (College of Family Physicians of Canada, 1993)
This article describes suggested treatment regimens for non-insulin-dependent diabetes mellitus. Diet is usually the first-line therapy. If this fails, most patients should be given a trial of oral agents, usually sulfonylurea first. Sulfonylurea and metformin can be combined if necessary. If oral agents fail, insulin is indicated. Insulin and an oral agent sometimes are used together.